Effect of vortex finder dimension on holdup mass and heat transfer rate in cyclone heat exchanger-CFD approach. (2018) - Mothilal, T.; Pitchandi, K.
This work investigates the effect of vortex finder dimensions on solid cyclone heat exchanger using Reynolds stress turbulence model (RSTM) in CFD code FLUENT 12. Seven cyclones were tested to find the holdup mass and amount of heat transferred from the inlet gas to solid particles. Tangential and axial velocity of cyclone reduces with increase in vortex diameter whereas increase in vortex finder length reduces tangential velocity slightly and not much variation is observed with axial velocity. The experimental data used for the validation of simulations were obtained from the literature study. Previous works done in varying the dimensions of vortex finder does not predict the holdup mass and heat transfer rate in cyclone. This work presents effect of vortex finder dimensions on holdup mass and heat transfer rate on solid cyclone heat exchanger. Holdup mass and heat transfer rate decreases with increase in both vortex finder diameter and vortex finder length. Results indicate that change in vortex finder diameter has more impact of about 25% to 48% than change in vortex finder length on holdup mass and about 3% to 5% on heat transfer rate.